Production of anti‐cancer immunotoxins in algae: Ribosome inactivating proteins as fusion partners. Issue 11 (25th June 2013) - Tran, Miller; Henry, Ryan E.; Siefker, David; Van, Christina; Newkirk, Greg; Kim, Julie; Bui, Jack; Mayfield, Stephen P.
ABSTRACT The eukaryotic green algae, Chlamydomonas reinhardtii has been shown to be capable of producing a variety of recombinant proteins, but the true potential of this platform remains largely unexplored. To assess the potential of algae for the production of novel recombinant proteins, we generated a series of chimeric proteins containing a single chain antibody (scFv) targeting the B‐cell surface antigen CD22, genetically fused to the eukaryotic ribosome inactivating protein, gelonin, from Gelonium multiflorm. These unique molecules, termed immunotoxins, are encoded as a single gene that produces an antibody—toxin chimeric protein capable of delivering a cytotoxic molecule to targeted B‐cells. We show that the addition of an Fc domain of a human IgG1 to these fusion proteins results in the production of assembled dimeric immunotoxins, containing two cell binding scFvs and two gelonin molecules. Additionally, we demonstrate that these algal expressed proteins are capable of binding and reducing the viability of B‐cell lymphomas, while treatment of T‐cells, that lack the CD22 antigen, had no impact on cell viability. Since other protein expression platforms are incapable of folding and accumulating these complex immunotoxins as soluble and enzymatically active proteins, our studies document a novel and efficient method for immunotoxin production. Biotechnol. Bioeng. 2013;110: 2826–2835. © 2013 Wiley Periodicals, Inc.